Book review: Adiloğlu, Adilhan. Ceditçilik Dönemi Kazan Tatar Edebiyatında Kadın Hak ve Hürriyetleri Meselesi (Аnkara: Gece Kitaplığı, 2020. 454 s.) - Aidar G. Khairutdinov (Историческая этнология, 2024)
The author of the review introduces the voluminous research work written by Adilkhan Adiloglu, a young Turkish scholar, and dedicated to the problem of women's rights and freedoms in the Tatar literature and periodicals of the Jadid era (mid-19th – early 20th centuries). The work’s value lies in the fact that, using rich factual material, the researcher presented the history of the emergence of the national-cultural revival among the Tatars and its outstanding participants. He managed to show the scale of participation of an educated Tatar Muslim woman in this process.